In Vitro Studies of Piperacillin, a New Semisynthetic Penicillin - Winston, Drew J. (1978)
Piperacillin, a new semisynthetic penicillin, was compared with other semisynthetic penicillins, cephalosporins, and aminoglycosides by the agar dilution method against 3,600 isolates of facultative gram-negative bacilli, Bacteroides fragilis, and enterococci. At 64 μg/ml, piperacillin inhibited 90% of the isolates in each group of organisms tested except for Escherichia coli (83% inhibited by 64 μg/ml). Compared with carbenicillin, piperacillin had a 16-fold increase in activity by weight against Pseudomonas aeruginosa and the enterococcus, an 8-fold increase against Serratia marcescens, and a 4-fold increase against B. fragilis and Enterobacter species. Piperacillin was highly active against carbenicillin-resistant Klebsiella pneumoniae and inhibited many aminoglycoside-resistant organisms. Except for P. aeruginosa, the minimum bactericidal concentration of piperacillin was usually within one tube dilution of the minimum inhibitory concentration. Approximately one-third of the gram-negative bacilli were inhibited synergistically by piperacillin plus amikacin, but no synergy could be demonstrated against enterococci. Piperacillin's in vitro activity against gram-negative bacilli was similar to gentamicin's except that it also included B. fragilis, and piperacillin was decidedly superior to presently available penicillins against K. pneumoniae.